Decomposition based least squares iterative estimation algorithm for output error moving average systems. Issue 4 (2014) - ,
Abstract : Purpose – The purpose of this paper is to solve the heavy computational problem of parameter estimation algorithm.Design/methodology/approach – Presents a decomposition least squares based iterative identification algorithm.Findings – Can estimate the parameters for linear or pseudo‐linear systems and have lower computational burden.Originality/value – This paper adopts a decomposition technique to solve engineering computation problems and offers a potential and efficient algorithm. Acknowledgements : This work was supported by the National Natural Science Foundation of China.